Comprehensive evaluation of geological and engineering factors affecting fracturing effectiveness in tight sandstone reservoirs - Hang SU; Ruixue LI; Hucheng DENG; Yuanwei QIN; Meiyan FU; Jianhua HE; Qinggao ZENG; Linke SONG; Jiawei ZHANG (Shiyou shiyan dizhi)
China's tight sandstone reservoirs possess immense hydrocarbon reserves with substantial development potential. Hydraulic fracturing in horizontal wells is a crucial enhancement method for developing these reservoirs. In tight sandstone reservoirs of the Jurassic Shaximiao Formation of the J gas field in the transitional zone between central and western Sichuan, differences in rock mechanical properties and geomechanical characteristics result in significant variations in fracturing effectiveness across wells despite similar fracturing processes. To enhance the effectiveness and specificity of fracturing, this study examined the impact of three geological factors—brittleness index, minimum horizontal principal stress, and differences between two horizontal principal stresses—on fracturing effectiveness. Based on the difference in horizontal principal stress, the geological conditions in the study area were classified into two categories, type Ⅰ and type Ⅱ, from favorable to less favorable. The influence of various engineering factors on fracturing effectiveness under these two types of geological conditions was analyzed, and optimal ranges for engineering parameters under these conditions were proposed. The Analytic Hierarchy Process (AHP) and Grey Relational Analysis (GRA) were employed to calculate the influence weight of each geological and engineering parameter on fracturing effectiveness, and then a quantitative evaluation model was established. Based on the correlation with fracturing effectiveness, the AHP-based model was selected as the optimal method to evaluate the fracturing effectiveness in the study area. It was also used to verify the rationality of the proposed ranges for engineering parameters outlined in the study and the applicability of the comprehensive evaluation model for fracturing effectiveness. This paper revealed significant differences in the suggested parameter ranges for horizontal well fracturing engineering under different geological conditions, with notably broader ranges for wells in more favorable conditions than those in less favorable ones. The AHP-based model was identified as the optimal geological and engineering comprehensive evaluation model for assessing the fracturing effectiveness in the study area.